2023
DOI: 10.23887/jet.v7i2.62728
|View full text |Cite
|
Sign up to set email alerts
|

Correlational Study: Teacher Perceptions and The Implementation of Education for Sustainable Development Competency for Junior High School Teachers

Abstract: ESD competence is key for teachers to implement ESD in schools so that education can make a real contribution to achieving sustainable development goals. This study analyzes the relationship between perceptions of teacher ESD competence and ESD implementation in Junior High Schools (JHS). This study uses a correlational study. The population in this study included JHS teachers. The research sample consisted of 384 teachers who were taken using a multistage sampling technique by taking teachers from 3 sub-distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Sustainable development competencies can be included in the development of academic programs. Learning model based on interdisciplinary learning with science interdisciplinary [42], problem-based [43], project based [44], as well as adopting sustainable development goals effective for increasing interdisciplinary thinking and environmental literacy of prospective teachers [45]. Teachers' integrated knowledge influences interdisciplinary learning so that the formation of interdisciplinary thinking skills is the initial stage carried out at universities in lectures.…”
Section: Resultsmentioning
confidence: 99%
“…Sustainable development competencies can be included in the development of academic programs. Learning model based on interdisciplinary learning with science interdisciplinary [42], problem-based [43], project based [44], as well as adopting sustainable development goals effective for increasing interdisciplinary thinking and environmental literacy of prospective teachers [45]. Teachers' integrated knowledge influences interdisciplinary learning so that the formation of interdisciplinary thinking skills is the initial stage carried out at universities in lectures.…”
Section: Resultsmentioning
confidence: 99%
“…Descriptive correlational studies do not involve manipulating conditions, aligning with the objectives of describing teachers' perceived levels of readiness and challenges in implementing inclusion, and analyzing relationships between these variables and teacher profiles. Correlational designs are commonly used when exploring relationships between teacher perceptions or attributes and implementation of educational practices (Mulyadi et al, 2023;Thomas, 2022). Similarly, this study aimed to examine connections between teacher perceptions of their own readiness and the barriers they faced promoting inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…Eliyawati et al [38] also emphasized the need for science teachers to integrate ESD teaching competencies with their science teaching competencies. In a dissimilar context, Mulyadi et al [39] found that teachers' perceptions of their ESD competence were positively correlated with the implementation of ESD in schools. Given these dynamics in the association of teachers' knowledge of ESD and their preparedness to engage in ESD, we hypothesize the following:…”
Section: Research Framework and Hypothesis Developmentmentioning
confidence: 99%